Building a Road Intersection Information System Based on Adobe Flash CS6 for Early Childhood Education - izmu, adam; Ari, Setiawan; Purnomo, Hendri (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2024)
In the current era of advanced and developing technology, the road crossing system is the most important part of city infrastructure whose aim is to ensure the safety of other road users. In recent years, technological developments have provided opportunities to increase efficiency so that road crossing system safety can be achieved. One of the technologies that can be utilized is Adobe Flash CS6 which is used by researchers to create interactive and attractive user interfaces. This research aims to develop a road crossing system based on Adobe Flash CS6. The research steps used the MDLC (Multimedia Development Life Cycle) method, including analyzing user needs, designing an intuitive user interface, implementing interactive features using Adobe Flash CS6, as well as testing and evaluating system performance. The main goal of this research is to create a more interactive and intuitive road crossing system using Adobe Flash CS6 technology. This information system is expected to increase road use awareness of traffic rules, thereby reducing the risk of accidents. By implementing a road crossing system based on Adobe Flash CS6, several good results can be achieved. Increased user awareness of traffic safety through an interactive user interface. Increased efficiency of the road crossing system through features designed to optimize pedestrian traffic flow. Reducing the risk of accidents at road crossings through the use of more sophisticated and intuitive technology. It is hoped that the results of this research can make a positive contribution to the safety and efficiency of road crossing systems in urban areas. This information system can be updated according to the wishes and needs of the responsible local government.